An Analysis of the Integration of Islamic Values in Science Learning at State Islamic Junior High School - Handoko, Akbar; Febtiana, Dwi; Hidayah, Nur; Haka, Nukhbatul Bidayati; Mazalena, Mazalena; Darmayanti, Heti (Biosfer: Jurnal Tadris Biologi, 2024)
Natural Sciences is one of the subjects studied in schools related to Islamic science. Therefore, it should not be seen as a discipline. Rather, it requires the integration of related Islamic values. This research aims to find out the extent of the process of integrating Islamic values in science learning. This research is a qualitative descriptive research with content analysis techniques. The results of the research showed that the integration of Islamic values in science learning in Madrasah includes: (1) The teachers' strategies used is the uswatun hasanah method; (2) The implementation in science learning is done by placing the Qur'an as a source of inspiration and confirmation; (3) The inhibiting factor is the teacher's educational background so that it affects the limitations of religious knowledge. Furthermore, the supporting factor is the many references to Qur'anic verses integrated into science materials. This research is only limited to showing the facts in the field. Therefore, follow-up research is needed on the integration of Islamic values in science learning.ABSTRAK: Ilmu Pengetahuan Alam merupakan salah satu mata pelajaran yang dipelajari di sekolah yang berkaitan dengan ilmu pengetahuan islam, oleh karena itu hendaknya tidak dipandang sebagai suatu disiplin ilmu melainkan diharuskan adanya integrasi nilai keislaman yang dikaitkan. Penelitian ini bertujuan untuk mengetahui sejauh mana proses integrasi nilai-nilai keislaman dalam pembelajaran IPA. Jenis penelitian ini adalah penelitian deskriptif kualitatif dengan teknik analisis konten pembelajaran. Hasil penelitian menunjukan bahwa integrasi nilai-nilai keislaman dalam pembelajaran IPA di Madrasah di antaranya adalah: (1) Strategi  guru menggunakan metode uswatun hasanah; (2) Implementasi dalam pembelajaran IPA dengan meletakkan Al-Qur’an sebagai sumber inspirasi dan konfirmasi; (3) Faktor penghambat yaitu latar pendidikan guru, sehingga mempengaruhi keterbatasan ilmu agama, sedangkan pendukung berupa referensi yang sudah banyak mengenai Ayat-Ayat Al-Qur’an yang diintegrasikan ke dalam materi IPA. Penelitian ini hanya sebatas menunjukkan fakta yang terdapat di lapangan. Oleh karena itu diperlukan penelitian tindak lanjut mengenai integrasi nilai keislaman pada pembelajaran IPA.